2015
DOI: 10.1017/s0022377815001051
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of runaway electron generation by massive helium injection after induced disruptions on TEXTOR

Abstract: Disruptions with runaway electron generation have been deliberately induced by injection of argon using a disruption mitigation valve. A second disruption mitigation valve has been utilised to inject varying amounts of helium after a short time delay. No generation of runaway electrons has been observed when more than a critical amount of helium has been injected no later than 5 ms after the triggering of the first valve. The required amount of helium for suppression of runaway electron generation is up to one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…It is suggested that the separation of the primary generation and the RE avalanche onset gives a narrow time window to suppress seed REs with a lower electron density before the RE avalanche onset, which will be much less than the previous prediction of the Rosenbluth no-avalanche density, ∼10 22 m −3 , for ITER [2]. The expected method for RE suppression appears to be consistent with the observation in the TEXTOR mitigation experiments, in which no generation of REs has been observed during disruptions when more than a critical amount of helium has been injected no later than 5 ms after the triggering of the first valve [33].…”
Section: Discussionsupporting
confidence: 79%
“…It is suggested that the separation of the primary generation and the RE avalanche onset gives a narrow time window to suppress seed REs with a lower electron density before the RE avalanche onset, which will be much less than the previous prediction of the Rosenbluth no-avalanche density, ∼10 22 m −3 , for ITER [2]. The expected method for RE suppression appears to be consistent with the observation in the TEXTOR mitigation experiments, in which no generation of REs has been observed during disruptions when more than a critical amount of helium has been injected no later than 5 ms after the triggering of the first valve [33].…”
Section: Discussionsupporting
confidence: 79%
“…The number of injected Argon particles in the three discharges is the same. The maximum electron density mainly depends on the number of injected Argon particles (Bozhenkov et al 2008;Lvovskiy et al 2015). Meanwhile, the loop voltages in the three discharges, measured by the flux loop mounted internal to the vacuum vessel and shown in Fig.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
“…When we take E = ηj at the TQ where j is the plasma current density and η the Spitzer resistivity, E ∝ − T e 7 show that more RE current is formed with higher temper ature (or lower electron density) before disruptions, which could not be simply explained only by the Dreicer mechanism. Moreover, the plasma electron density evolution during the disruptions mainly depends on the number of injected argon particles [36]. The electron density and its temporal change during the disruption in the two shots are similar due to the same amount of argon injection, showing a strong increase with respect to the pre-disruption electron density.…”
Section: Re Generation Dependence On Pre-disruption Electron Densitymentioning
confidence: 95%